KAJIAN YURIDIS TERHADAP RISIKO KREDIT BANK YANG TIMBUL DARI KEPAILITAN PERUSAHAAN BESAR: KASUS PT SRITEX - Danang Catur Wahyu Wijayanto (Journal of Innovation Research and Knowledge, 2025)
This study discusses the legal analysis of bank credit risks arising from the bankruptcy of large companies, with a case study of PT Sritex. The bankruptcy of Sritex in 2024–2025 caused significant losses to creditor banks, particularly Bank DKI and Bank BJB, due to irregularities in the credit granting procedures and weak internal and external supervision. This study employs a literature review method. The findings reveal that although legal protection for banks as creditors is regulated under the Bankruptcy Law and banking regulations, its implementation still faces challenges in terms of collateral enforcement, regulatory harmonisation, and oversight of credit fund usage. This study recommends the need for revisions and harmonisation between the Bankruptcy Law and the Banking Law, real-time monitoring of credit fund flows by the OJK, and stricter enforcement of administrative sanctions to prevent the recurrence of similar credit risks in the future